Code Switching in the Movie The Godfather by Mario Puzo and Francis Ford Coppola - Adhitya Putra, Gede Nyoman (Humanis; Vol 22 No 1 (2018)DO - 10.24843/JH.2018.v22.i01.p40, 2018)
The study entitled Code Switching in the Movie The Godfather by Mario Puzo and Francis Ford Coppola is aimed at identifying and analyzing types and reasons for code switching which are found in the trilogy movie ‘The Godfather’. The data of this study are the trilogy movie adapted from novels by Mario Puzo; The Godfather (1972), The Godfather II (1974), and The Godfather III (1990), as long as the transcript of each movie transcribed Malta. Data of this study are in the form of utterances spoken by the characters found within the transcript and the movies. The is analyzed using the theory of types of code switching proposed by Poplack (Romaine, 1995), theory of reasons for code switching proposed Grosjean (1982), and theory of four factors which cause the change of codes and varieties proposed by Tripp (Grosjean, 1982). The data were collected by doing observation and documentation. The result of this study shows that three types of code switching, and nine out of ten reasons for code switching are found within the data; as well as four other reasons are found in the data using the theory of four factors which cause the change of code and varieties, they are (1) show close relationship between participants, (2) to convince or persuade other participants, (3) habit of using more than one language in conversation, and (4) show-off .